Język blogów a normy poprawnościowe języka polskiego - Szczerbal, Magdalena; Kamasa, Victoria (Investigationes Linguisticae, 2012)
This article presents results of exploratory study concerning the relation between Polish language norms and texts published on weblogs. Six weblogs were analyzed in order to find all differences between the forms used on the blogs and those suggested by norms. Those differences were then classified as either justified innovation or mistakes. The classification on found mistakes based on the literature was also conducted.